Expression of mannose receptor and ligands for its cysteine-rich domain in venous sinuses of human spleen. - Martinez-Pomares, L; Hanitsch, L; Stillion, R; Keshav, S; Gordon, S (2005)
The mannose receptor (MR) is a type I membrane molecule with two lectin activities. Mannose recognition takes place through the C-type lectin-like carbohydrate recognition domains, while recognition of sulphated glycans is mediated by the cysteine-rich domain (CR). In murine spleen CR ligands are present in a subpopulation of macrophages (Mphi) placed in the marginal zone whereas MR-expressing cells consisting of Mphi and nonvascular endothelia are located in the red pulp. No colocalisation of MR with CR ligands has been observed in murine tissues. In this manuscript we describe the distribution of MR and CR ligands in human spleen. In this organ we have detected a perfect colocalisation of MR with CR ligands in Lyve-1+ cells lining venous sinuses. These cells form a physical barrier for blood cells as they need to migrate through the sinuses in order to exit the splenic parenchyma and, in this way, contribute to the unique filtration function of this organ. Furthermore, unlike murine spleen, CD68+ red pulp Mphi lack MR expression. Our results suggest an unexpected contribution of MR to splenic function through the recognition of sulphated ligands that could influence the filtering capability of this organ.